Optimization pH of Enzymatic Hydrolysis of Endo-1,4-Î²-Xylanase for Xylooligosaccharides Production - Ratnadewi, Anak Agung Istri; Kurniawan, Andika Ade; Handayani, Wuryanti (UNEJ e-Proceeding, 2014)
Xylooligosaccharides (XOS) with polymerisation degree between 2 till 10 monomerÂ  have prebiotic effect for better digestion system. In this research, production of XOS was performed by enzymatic hydrolysis of xylan with endo-1,4-Î²-xylanases enzyme. Endo 1,4-Î²-xylanases enzyme was aqcuired from Bacillus sp. isolated from termiteâs abdominal.Meanwhile oat xylan was used as substrate. Optimal condition of enzymatic hydrolysis was evaluated at pH: 4, 5, 6, and 7 with incubation time from 5 to 20 h.pH 5 was optimum pH to produce XOS from 0.8 % xylan oat at 40 oC.The hydrolysis product purified and analyzed by thin layer chromatographyyielding spot of xylobiose, xylotriose, xilotetraose and xilopentaose. Further analysis by HPLC indicated dominant xilopentaosa X5 (3522 ppm) among Â the other XOSÂ Â  X2 (14 ppm), X3 (43 ppm) and X4 (15 ppm). Keywords: Xylooligosaccharides, endo-1,4-Î²- endoxylanase